Analysis of Unsafe Actions and Unsafe Conditions in the Fleet of PT Pertamina International Shipping - casmono, isma kurnia; Simanjuntak, Marihot; Sibarani, Mauritz H. M Sibarani; Hidayat, Arif; Nasri (Meteor STIP Marunda, 2023)
This study aims to identify the level and the primary causes of unsafe actions and unsafe conditions in the fleet operated by PT Pertamina International Shipping. The research employed a descriptive qualitative approach, emphasizing the observation of unsafe actions and unsafe conditions while collecting in-depth data to obtain factual information, justify existing conditions, conduct evaluations, and provide a comprehensive understanding of the issues. Data were collected through observations of reported unsafe actions and unsafe conditions from vessels operated by PT Pertamina International Shipping. The researcher analyzed these reports and drew conclusions based on the findings. In addition, a literature review was conducted by examining relevant references, including the company's Safety Management System (SMS) Manual and Basic Safety Training (BST) manuals.